Limpeza do forame e extrusão apical de raspas de dentina em dentes unirradiculares submetidos ao procedimento de patência apical - Ribeiro, Ana Paula Dias [UNESP]; Malnati, Priscila de Souza; Costa Júnior, Edson Dias (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2010)
Objective: To verify the cleaning of the apical foramen and apical extrusion of dentin chips in single-rooted teeth instrumented with two techniques, one of which including the apical patency procedure. Method: Thirty teeth were internally stained with Indian ink, divided in two groups, of which only group I was subjected to apical patency. The dentin chips extruded through the apical foramen were collected in a glass receptacle and quantified. The apical foramen region was divided in quadrants and analyzed with a stereomicroscope to verify the action of the instrument on the cemental canal walls. The teeth were scored 0 4 according to the number of clean walls (without Indian ink), 0 corresponding to no clean wall. Results: In group I, there was no dentin plug, but only 1 tooth was scored 4. In group II, 10 teeth presented dentin plug and all of them were scored 0. There was no statistically significant difference between groups I and II regarding the extruded dentin mass (Scheffé test; p<0.05). Conclusion: The use of the apical patency procedure in single-rooted teeth does not modify the amount of dentin chips extruded through the apical foramen, does not produce an adequate cleaning of the cemental canal walls, but remove the plug of dentin chips from the cemental canal.
Cleaning of the foramen apical and apical extrusion of dentin chips in single-rooted teeth subjected to apical patency